Social and Psychological Factors of Migration Readiness of Ukrainian Students - Цільмак, Олена Миколаївна; Цільмак, О. М.; Цильмак, Елена Николаевна; Tsilmak, Olena M.; Блинова, Олена Євгенівна; Блинова, О. Є.; Блинова, Елена Евгеньевна; Blynova, Olena Ye.; Попович, Ігор Степанович; Попович, І. С.; Попович, Игорь Степанович; Popovych, Ihor S.; et al. (Revista Espacios, 2019)
The paper examines the problem of social and psychological factors of labor migration of Ukrainian citizens. It defines the concept “migration readiness” and looks at the features of migration readiness of Ukrainian university students. The paper presents the results of the authors’ social and psychological research aimed at identifying the attitude towards labor migration, the evaluation of its consequences for the country, families and individuals, the reasons and possibilities of self-realization abroad. It was determined that the students are guided by higher salaries and wages abroad and new experience, in this situation the evaluation of occupational prestige and the possibility to increase social status are rather insignificant, that leads to the students’ understanding of the Ukrainians’ labor migration as a necessary measure, which is caused by the necessity to meet an individual’s basic needs.

У роботі розглядається проблема соціально-психологічних факторів трудової міграції громадян України. Дано визначення поняття «міграційна готовність» та розглянуто особливості міграційної готовності студентів українських ЗВО. У роботі представлено результати соціально-психологічних досліджень авторів, спрямованих на виявлення ставлення до трудової міграції, оцінку її наслідків для країни, сім’ї та окремої людини, причин і можливостей самореалізації за кордоном. Визначено, що студенти орієнтуються на вищі зарплати за кордоном та новий досвід, у цій ситуації оцінка професійного престижу та можливості підвищення соціального статусу є досить незначною, що призводить до розуміння студентами трудової міграції українців як необхідного заходу, який зумовлений необхідністю задовольнити базові потреби особи.
Blynova O. Social and Psychological Factors of Migration Readiness of Ukrainian Students / O. Blynova, I. Popovych, H. Bokshan, O. Tsilmak, N. Zavatska // Espacios. – Vol. 40. - № 36. - Revista Espacios, 2019. - 10p.
Keywords: labor migration; migration readiness; migration motivation; university students; трудова міграція; міграційна готовність; міграційна мотивація; студенти ЗВО; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology